Factor Analysis of Metabolic Syndrome in Aged Population Undergoing Periodical Health Examinations (International Journal of Studies in Nursing, 2020)
Background: Metabolic syndrome (MetS) is a common health problem in aged people. The cluster of diseases associated with MetS, namely, heart disease, cerebrovascular disease, diabetes, hypertensive disease and renal disease, had made a death rate of 0.17%, higher than 0.15% attributed to cancers. Aims: To investigate the prevalence, incidence and reversion rate of MetS in Aged population undergoing periodical health examinations, as well as the associated impact factors. Results: The prevalence of MetS was found to be 19.9% among all the subjects studied, to be higher in female (23.1%) than in male (18.3%). The incidence of MetS was 17.6%. In contrast, the reversion rate of MetS was